From self-fulfilling mistakes to behavioral learning equilibria - Cars Hommes (Tinbergen Institute, 2017)
This essay links some of my own work on expectations, learning and bounded rationality to the inspiring ideas of Jean-Michel Grandmont. In particular, my work on consistent expectations and behavioral learning equilibria may be seen as formalizations of JMG's ideas of self-fulfilling mistakes. Some of our learning-to-forecast laboratory experiments with human subjects have also been strongly influenced by JMG's ideas. Key features of self-fulfilling mistakes are multiple equilibria, excess volatility and persistence amplification.
Keywords: D84; D83; E32; C92; 330; expectations; learning; bounded rationality; chaos; almost self-fulfilling equilibria; laboratory experiments